ANALYSIS OF THE FEASIBILITY STUDY OF CATFISH BREEDING BUSINESS IN SIPANGE GODANG VILLAGE - Hesti Rauli; Sry Lestari; Muhammad Arif (PT. Jurnal Center Indonesia Publisher, 2026)
The catfish hatchery business has quite good market opportunities due to the increasing public demand for catfish as a widely consumed food source. This study aims to analyze the feasibility of the catfish hatchery business in Sipange Godang Village in terms of non-financial aspects, financial aspects, and sharia principles. This study uses a descriptive research type with a qualitative approach. The research informants were three catfish hatchery entrepreneurs selected using a saturated sampling technique. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The business feasibility analysis was carried out based on legal, market and marketing, technical, management, socio-economic, environmental, and financial aspects using the Payback Period (PP), Break Even Point (BEP), and Revenue Cost Ratio (R/C Ratio) methods. The results of the study indicate that the catfish hatchery business in Sipange Godang Village is feasible to be run and developed. Viewed from the non-financial aspect, the business has fulfilled the legal, market and marketing, technical, management, socio-economic, and environmental aspects, although strengthening the business legality is still needed. From a financial perspective, the business is able to recoup its capital, sales are above the break-even point, and its R/C ratio is greater than 1, making it financially viable. Based on Sharia principles, the business is run honestly and free from riba, maysir, and gharar.